Bibliometric trends of South African environmental health articles between 1998 and 2015: Making local research visible and retrievable - Wright, C Y; Dominick, F; Kunene, Z; Kapwata, T; Street, R A (South African medical journal, 2017)
South Africa (SA) has to grapple with multiple burdens of disease for which environmental factors have a role to play in both causation and prevention. This article describes a bibliometric review of environmental health indexed literature for SA over an 18-year period. To provide an overview of the nature of SA-based published environmental health indexed research and to identify search challenges, frequently researched topics, and gaps and opportunities for future research. The Web of Science, PubMed and Science Direct were used to search for original, peer-reviewed and review articles with the inclusion criteria 'environmental health' and 'South Africa' available online and published between 1998 and 2015, inclusively. A total of 230 journal articles were included in the bibliometric analysis. The highest number of articles (n=54) was published in 2015. The majority of the first authors were affiliated with SA institutions (n=160, 69.5%). For the articles where funding was explicitly declared (n=148), the three most frequently occurring agencies that funded the published research were the National Research Foundation in SA (n=17), the South African Medical Research Council (n=13) and the Water Research Commission (n=9). There was little inter-annual/environmental health category variation over time owing to the relatively small sample size. The largest number of retrieved journal articles was in the area of environmental pollution control (n=76), followed by environmental health lifestyle and behaviour-related topics (n=42) and then water monitoring (n=26). Despite the research needed to solve large environmental health challenges in SA, environmental health was only used as a keyword in title, author keywords or abstract for 230 SA-based studies over an 18-year period. This makes it extremely difficult for environmental health research to be located and used to inform the profession as well as the research agenda. Several issues that environmental health practitioners are typically tasked to implement and monitor are not indexed as environmental health topics. The need for authors to use 'environmental health' as a keyword is emphasised, particularly if research is to inform decision-making and policy support, as well as guide future research in the country.